2022
DOI: 10.3368/jhr.1020-11266r2
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Maternal Smoking and Genes in Offspring Birth Weight

Abstract: It is well-established that birth weight is affected by the child's genetic endowments and maternal smoking during pregnancy. Here, we investigate whether an interaction between genetic endowments and maternal smoking on birth weight exists. We instrument the maternal smoking decision with a genetic variant (rs1051730) located in the nicotine receptor gene CHRNA3 and deal with the underreporting of maternal smoking by using a biomarker of nicotine collected during pregnancy. We confirm that genetic endowments … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…Despite not being able to detect a meaningful genetically moderated exposure effect, overall our results suggest that smoking before pregnancy or smoking in the first three months of pregnancy results in a lower birth weight compared to not smoking. This is in line with previous publications [26, 19, 8].…”
Section: Applied Examplesupporting
confidence: 94%
See 1 more Smart Citation
“…Despite not being able to detect a meaningful genetically moderated exposure effect, overall our results suggest that smoking before pregnancy or smoking in the first three months of pregnancy results in a lower birth weight compared to not smoking. This is in line with previous publications [26, 19, 8].…”
Section: Applied Examplesupporting
confidence: 94%
“…Instances of genetically driven effect heterogeneity do exist in main stream epidemiological investigations of non-pharmaceutical interventions. For example, smoking in pregnancy has been shown to have measurable consequences on offspring b irth w eight, w hich i s a n i mportant m arker o f l ong-term h ealth [8]. Specifically, Freathy et al [9] show that single-nucleotide polymorphism (SNP) rs1051730 on chromosome 15 is associated with smoking cessation during pregnancy as well as smoking quantity.…”
Section: Introductionmentioning
confidence: 99%
“…Causal evidence on genetic heterogeneities relating to smoking behaviours is sparse since this area of research is still relatively young. Pereira et al (2022) examine whether the causal effects of maternal smoking on birth weight differ by genetic ‘predisposition’ for smoking, but find no evidence of such gene-environment interactions.…”
Section: Discussionmentioning
confidence: 99%
“…These associations were robust to controlling for a range of confounders such as maternal age, parity and social circumstances (Lowe, 1959). Since then, many subsequent studies have shown the adverse impacts of in utero exposure to tobacco and cigarette smoke on outcomes around birth (e.g., birth weight; Rantakallio, 1978b; Walker et al, 2009; Yang et al, 2020; Pereira et al, 2022) but also the impacts of prenatal smoking on outcomes in the longer run (e.g., hospital admissions, childhood height, educational outcomes, child behaviour; Butler and Goldstein, 1973; Rantakallio, 1978a; Dolan et al, 2016). 1 While the harmful effects of smoking during pregnancy are well-known today and maternal smoking rates are lower than decades ago (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, the NHS digital service provides statistics indicating that approximately 8.6 % of mothers were known smokers at the time of delivery in the first half of 2023 2 . Mendelian Randomization studies between smoking during pregnancy and offspring birth weight suggest a causal relationship between smoking during pregnancy and lower birth weight [3][4][5][6] . However, the underlying mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%